2014
DOI: 10.1115/1.4027669
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of a New Carbon Fiber/Flax/Epoxy Bone Fracture Plate Shows Less Stress Shielding Compared to a Standard Clinical Metal Plate

Abstract: Femur fracture at the tip of a total hip replacement (THR), commonly known as Vancouver B1 fracture, is mainly treated using rigid metallic bone plates which may result in "stress shielding" leading to bone resorption and implant loosening. To minimize stress shielding, a new carbon fiber (CF)/Flax/Epoxy composite plate has been developed and biomechanically compared to a standard clinical metal plate. For fatigue tests, experiments were done using six artificial femurs cyclically loaded through the femoral he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 55 publications
4
64
0
Order By: Relevance
“…Not only did the current CF/ Flax/Epoxy has promising biological properties, but the present authors previously showed it has lower axial stiffness (for reducing "stress shielding") and adequate bending stiffness (for proper fracture site immobilization) [11]. Moreover, in a prior biomechanical study, the current authors have used this plate to fix a Vancouver B1 femoral fracture under clinical-type static and dynamic loading conditions with comparable results to a medical grade 316L stainless steel fixation plate [50].…”
Section: Practical Implicationsmentioning
confidence: 71%
See 2 more Smart Citations
“…Not only did the current CF/ Flax/Epoxy has promising biological properties, but the present authors previously showed it has lower axial stiffness (for reducing "stress shielding") and adequate bending stiffness (for proper fracture site immobilization) [11]. Moreover, in a prior biomechanical study, the current authors have used this plate to fix a Vancouver B1 femoral fracture under clinical-type static and dynamic loading conditions with comparable results to a medical grade 316L stainless steel fixation plate [50].…”
Section: Practical Implicationsmentioning
confidence: 71%
“…stiffness) for almost 90% of its fatigue life, which is almost never the case for homogeneous metallic materials [26]. More importantly, as a consequence of its biomechanical properties, this composite can potentially minimize the common major problem of "stress-shielding", which is typically present when using metallic materials to fix bone fractures [27]. Also, this composite provides adequate immobilization that avoids any gross motion at the fracture site leading to proper healing of the fractured bone [27].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The second type of heat source is friction inside the material or between the support and the test specimen. While the generation of heat due to the latter is a general problem especially during fatigue testing of composites [199][200][201], the friction inside the material is key to assist in interpretation of material failure. During periodic cyclic loading experiments, existing crack surfaces can rub against each other and therefore generate a noticeable amount of heat.…”
Section: Thermographymentioning
confidence: 99%
“…The modulus for a metal bone plate is between 110 GPa and 220 GPa compared to human long cortical bone of around 17–20 GPa [ 66 ]. Cellular bone formation and bone loss are balanced so that when higher loads are applied osteogenic bone formation occurs to counteract the extra force [ 65 67 ]. Consequently, with metal plates, the bone fracture is “shielded” or under-stressed and prevented from healing normally even for tissues ingrown into the fracture site by resorbing into weaker bone according to Wolff's law [ 65 67 ].…”
Section: Biomaterials Implant Considerationsmentioning
confidence: 99%